Dominions: Original Correspondence - Great Britain. Colonial Office; Australian Joint Copying Project; National Library of Australia; Library of New South Wales; Great Britain. Public Record Office (Canberra : Australian Joint Copying Project, 1907)
Correspondence of the Dominions Office of the Colonial Office consisting of despatches and their enclosures from the governors of Dominions and letters and reports from British government agencies, miscellaneous institutions and individuals in Britain or overseas, concerning the Dominions.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Australian Joint Copying Project handbook. Part 2 : Colonial Office - class and piece list
Public Record Office CO 532.
Also available online
Original held by Public Record Office, London.
Keywords: Great Britain. -- Colonial Office -- Archives; Great Britain -- Politics and government -- 1901-1936.; Commonwealth countries -- Politics and government